PENINGKATAN KESADARAN BAYAR PAJAK KENDARAAN BERMOTOR DI KOTA PALANGKA RAYA; PENTINGNYA EDUKASI PAJAK BAGI GENERASI MUDA - Pebrianti , Anisa; Rafsanjani, Muhamad Arief; Retei Alfri Sandi, Jhon (Jurnal Abdimas Bina Bangsa, 2025)
Regional taxes are one of the important sources of regional revenue to improve services to the community in the implementation of development, which is carried out based on the principles of democracy, equity, justice, community participation and accountability by paying attention to regional potential. Motor vehicle taxes have the potential to increase the rate of regional improvement, as it is an obligation that must be fulfilled by individuals who own motor vehicles. The younger generation who own motorized vehicles often do not care and understand the term taxpayers. The young generation in the city of Palangka Raya must receive maximum education about the importance of paying taxes that have benefits for the common good and welfare of the community. It is hoped that education and information about the importance of taxpayer awareness can increase understanding and knowledge, especially for the younger generation. Based on the results of the evaluation, as many students have knowledge